2014
DOI: 10.1785/0120130103
|View full text |Cite
|
Sign up to set email alerts
|

The Largest Expected Earthquake Magnitudes in Japan: The Statistical Perspective

Abstract: Earthquake catalogs are probably the most informative data source about spatiotemporal seismicity evolution. The catalog quality in one of the most active seismogenic zones in the world, Japan, is excellent, although changes in quality arising, for example, from an evolving network are clearly present. Here, we seek the best estimate for the largest expected earthquake in a given future time interval from a combination of historic and instrumental earthquake catalogs. We extend the technique introduced by Zöll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The largest earthquake of which we are aware that took place in this location is the 2011 M w 9 Tohoku-Oki event, so here we have a high lower bound for M max . Previous estimates for M max varied from 9 (McCaffrey, 2008, using scaling relations and fault segment lengths) to 10 (if confidence limits are high) (Zöller et al, 2014, using the tapered GR distribution, but not conservation of moment). Using the theory of extreme values, Pisarenko et al (2010) found the absolute M max to be 9:57 0:86 for Japan.…”
Section: Japan Trenchmentioning
confidence: 99%
“…The largest earthquake of which we are aware that took place in this location is the 2011 M w 9 Tohoku-Oki event, so here we have a high lower bound for M max . Previous estimates for M max varied from 9 (McCaffrey, 2008, using scaling relations and fault segment lengths) to 10 (if confidence limits are high) (Zöller et al, 2014, using the tapered GR distribution, but not conservation of moment). Using the theory of extreme values, Pisarenko et al (2010) found the absolute M max to be 9:57 0:86 for Japan.…”
Section: Japan Trenchmentioning
confidence: 99%
“…In addition, the observed rate estimated from the complete part of the Uhrhammer catalog since 330 is shown. Acknowledging concerns about assigning a maximum magnitude (Holschneider et al, 2011;Zöller et al, 2013Zöller et al, , 2014, we estimated a maximum magnitude using the Bayesian estimator by Kijko (2004) of M w 8. Inserting this estimate into the nontruncated version of the Gutenberg-Richter relation we obtained, we can estimate an average return period of an event larger than M w 8 as 660 years (Grünthal catalog; Uhrhammer catalog 1200) for the whole region.…”
Section: Smoothed-seismicity Source Modelsmentioning
confidence: 99%
“…Pisarenko et al decluster the earthquake catalog and use only the main events to provide a homogeneous Poisson process with independent magnitudes similar to e.g. Zöller et al (2014). But a homogeneous Poisson process is not a necessary condition for applying GEVD and GPD.…”
Section: Is a Homogeneous Poisson Process Needed?mentioning
confidence: 99%